OBSERVASI SUPERVISI KEPENDIDIKAN TERHADAP HASIL KOMPETENSI DAN KINERJA GURU DALAM KEGIATAN BELAJAR MENGAJAR - Suparti Suparti (Smart Education, 2020)
Abstract: The subjects of this study were teachers of SD Negeri 013887 Asahan Mati subdistrict Tanjung Balai district Asahan Academic Year 2019/2020. The location of this research was carried out at SD Negeri 013887 Asahan Mati subdistrict Tanjung Balai district Asahan. When the research was carried out from July 2019 to October 2019, it was obtained from the results of observations from the first cycle of the teacher's attitude in compiling good lesson units with an average of 62.17. The principal was very enthusiastic about carrying out the preparation of good lesson units compiled by teachers in the moderate category with an average of 68.33. The data obtained from the results of observations in cycle I and cycle II of teacher attitudes in compiling and practicing in class is quite good, with an average value of 84.22 teachers at SDN Negeri 013887 Asahan Mati subdistrict Tanjung Balai district Asahan was very enthusiastic about carrying out the preparation of lesson units and practicing them well. One step from the results of the assessment on the implementation in class is quite good. Paying attention to the results in cycle II reflecting on the results obtained by researchers in cycle II there has been an increase in the ability of teachers at SD Negeri 013887 Asahan Mati subdistrict Tanjung Balai district Asahan in compiling and practicing good lesson units even though they are not maximal, namely 8.00.Keywords: supervision, competence, performanceAbstrak: Subjek penelitian ini adalah Guru-guru SD Negeri 013887 Asahan Mati Kec. Tanjung Balai Kab. Asahan Tahun Pelajaran 2019/2020. Lokasi penelitian ini dilaksanakan di SD Negeri 013887 Asahan Mati Kec. Tanjung Balai Kab. Asahan. Waktu penelitian dilaksanakan pada bulan Juli 2019 s/d Oktober 2019. di peroleh dari hasil observasi dari siklus I ini sikap guru dalam menyusun satuan pelajaran yang baik â€œ nilai kurangâ€ dengan rata-rata 62.17. kepala sekolah sangat antusias melaksanakan penyusunan satuan pelajaran yang baik yang disusun oleh guru dalam kategori cukup dengan rata-rat 68.33. Data yang diperoleh dari hasil observasi pada siklus I dan siklus II sikap guru dalam menyusun dan memprektekkan dikelas cukup baik, dengan rata-rata nilai 84.22 guru-guru di SDN Negeri 013887 Asahan Mati Kec. Tanjung Balai Kab. Asahan sangat antusias melaksanakan penyusunan satuan pelajaran dan mempraktekkan nya dengan baik. Sedangkah dari hasil penilaian terhadap penilaian dalam implementatif di kelas cukup baik. Memperhatikan hasil pada siklus II melakukan refleksi terhadap hasil yang diperoleh peneliti pada siklus II ini sudah ada peningkatan kemampuan guru-guru SDN Negeri 013887 Asahan Mati Kec. Tanjung Balai Kab. Asahan dalam menyusun dan mempraktekkan satuan pelajaran yang baik walaupun belum maksimal yaitu 8.00.Kata kunci: supervise, kompetensi, kinerja